1994
DOI: 10.1177/104063879400600110
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Identification of Renibacterium Salmoninarum by Monoclonal Antibodies in Paraffin-Embedded Tissues of Atlantic Salmon (Salmo Salar L.), using Paired Immunoenzyme and Paired Immunofluorescence Techniques

Abstract: Abstract. Renibacterium salmoninarum was identified in situ by immunoenzymatic and immunofluorescence techniques in paraffin-embedded tissue specimens collected during a natural outbreak of bacterial kidney disease (BKD) and from an experimental infection in Atlantic salmon (Salmo salar L.). Monoclonal antibodies (MAbs) 4D3 and 2G5 were used in this study, both specific for the 57-58-kD outer membrane protein (p57) of the bacterium. Both MAbs revealed positive staining in ethanol-fixed tissue specimens, but on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…In case of the Iron River BKT mortalities, IHC stained slides indicated the presence of an intense distribution of bacterial cells and their antigens within the kidney tissues, as well as within the granulomas, which confirms the assumption that the severe progression of the disease is associated with high bacterial metabolic activities [26][27][28]. Similar findings were reached by [14,15]. Some discrepancies were observed between histopathological findings (positive with different scores) and IHC results (negative results with some of positive histopathological changes).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…In case of the Iron River BKT mortalities, IHC stained slides indicated the presence of an intense distribution of bacterial cells and their antigens within the kidney tissues, as well as within the granulomas, which confirms the assumption that the severe progression of the disease is associated with high bacterial metabolic activities [26][27][28]. Similar findings were reached by [14,15]. Some discrepancies were observed between histopathological findings (positive with different scores) and IHC results (negative results with some of positive histopathological changes).…”
Section: Discussionsupporting
confidence: 70%
“…In this context, Evensen et al [15] reported on their success in detecting R. salmoninarum in situ using paraffin embedded tissue specimens from infected Atlantic (Salmo salar). However, it has been reported that extended preservation of tissue samples in formalin has deleterious effect on the antigen detection and retrieval in IHC [14].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that formalin fixation reduces the sensitivity of immunohistochemical techniques compared to precipitating fixatives, when using immune sera or monoclonal antibodies against protein epitopes , Valnes et al 1984. The differences in detection sensitivity, ex-pressed as the smallest amount of antigen revealed (Petrusz et al 1980), may range from 3-to 8-fold between ethanol and formalin fixation when evaluated in artificial antigen media , Valnes et al 1984, Evensen et al 1994; the adverse effects induced by fixation, especially by the aldehyde-containing fixatives, include the masking of tissue antigens with loss of antigenicity. The most recent previous report on in situ den~onstration of VHS virus describes a higher sensitivity of immunofluorescence methods compared to virus isolation when physical fixation and frozen sections are used (Ortega et al 1992).…”
Section: Discussionmentioning
confidence: 99%
“…The biopsy instrument b was placed into the surgical incision and blindly directed caudodorsally through the pericardial sac and into the cranialmost aspect of the kidney tissue. The biopsy forcep was then closed, removing a small sample of kidney tissue (approximately 1.0-1.5 mm 3 ). An impression smear was made of the fluid from the lateral surface of the biopsy forceps and examined microscopically for the presence of melanin granules to confirm the presence of renal tissue within the biopsy forceps (Fig.…”
mentioning
confidence: 99%
“…Direct immunohistochemical procedures were performed as previously described, 3,5,10 Paraffin-embedded tissue sections were deparaffinized in an oven followed by 3 changes of toluene for 5 minutes each, 2 changes of 100% ethanol for 3 minutes each, and 2 changes of 95% ethanol for 3 minutes each. Slides were then rinsed in running water and incubated overnight in 5% hydrogen peroxide to remove melanin pigments.…”
mentioning
confidence: 99%